Polyploid origin and karyotype evolution in Myrsine L. - Carvalho, Renata Flávia de (2016)
Polyploidy plays a relevant role in the diversification and speciation of Angiosperms, including the family Primulaceae. Diploid, tetraploid and octaploid species are reported for the genera Cyclamen, Dodecatheon and Primula, but the evolutionary aspects